Realistic simulation is associated with healthcare professionals’ increased self-perception of confidence in providing acute stroke care: a before-after controlled study - Suzete Nascimento FARIAS DA GUARDA; João Pedro Souza SANTOS; Mariana Sampaio Motta REIS; Rogério da Hora PASSOS; Luis Claúdio CORREIA; Juliana Ribeiro CALDAS; André Luiz Nunes GOBATTO; Maurício TEIXEIRA; Adelmo OLIVEIRA; Michel Pordeus RIBEIRO; Paulo Benigno Pena BATISTA; Marcelo CALDERARO; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Simulations are becoming widely used in medical education, but there is little evidence of their effectiveness on neurocritical care. Because acute stroke is a neurological emergency demanding prompt attention, it is a promising candidate for simulation training. Objective: To assess the impact of a stroke realistic simulation course on clinicians’ self-perception of confidence in the management of acute stroke. Methods: We conducted a controlled, before-after study. For our intervention, 17 healthcare professionals participated in a stroke realistic simulation course. As controls, participants were chosen from a convenience sample of attendees to the courses Emergency Neurologic Life Support (ENLS) (18 participants) and Neurosonology (20 participants). All participants responded pre- and post-test questionnaires evaluating their self-perception of confidence in acute stroke care, ranging from 10 to 50 points. We evaluated the variation between pre- and post-test results to assess the change on trainees’ self-perception of confidence in the management of acute stroke. Multivariate analysis was performed to control for potential confounders. Results: Forty-six (83.63%) subjects completed both questionnaires. The post-test scores were higher than those from the pretests in the stroke realistic simulation course group [pretest median (interquartile range - IQR): 41.5 (36.7-46.5) and post-test median (IQR): 47 (44.7-48); p=0.033], but not in the neurosonology [pretest median (IQR): 46 (44-47) and post-test median (IQR): 46 (44-47); p=0.739] or the ENLS [pretest median (IQR): 46.5 (39-48.2), post-test median (IQR): 47 (40.2-49); p=0.317] groups. Results were maintained after adjustment for covariates. Conclusions: This stroke realistic simulation course was associated with an improvement on trainees’ self-perception of confidence in providing acute stroke care.